2010
DOI: 10.1515/text.2010.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and displaying suitability for adoptive parenthood: a conversation analysis of relationship questions and answers

Abstract: In this study we examine how suitability for adoptive parenthood is assessed and displayed in interactions between social workers and prospective adoptive parents. In particular, we have analyzed relationship questions that are put to couples with and without an observation from the social worker. The answers are featured as very precise, stressing the positive aspects of the relationship but avoiding sainthood, and accompanied with examples that illustrate the stability of the relationship. We concluded that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…The institutional setting might inhibit the achievement of a state of honest reflection in the interactions with the professional, which has also been noted by van Nijnatten (2010) in the context of child welfare. Earlier resistance and strategies by clients in child welfare have been identified by Smith (2008) and Dumbrill (2006), and in prospective adoptive parents by Noordegraaf et al (2010). Dumbrill (2006) names three strategies as 'playing the game, co-operate, or fight', all of which are connected to the different perception of the power usage of the professional.…”
Section: Discussionmentioning
confidence: 99%
“…The institutional setting might inhibit the achievement of a state of honest reflection in the interactions with the professional, which has also been noted by van Nijnatten (2010) in the context of child welfare. Earlier resistance and strategies by clients in child welfare have been identified by Smith (2008) and Dumbrill (2006), and in prospective adoptive parents by Noordegraaf et al (2010). Dumbrill (2006) names three strategies as 'playing the game, co-operate, or fight', all of which are connected to the different perception of the power usage of the professional.…”
Section: Discussionmentioning
confidence: 99%
“…Fear in this controlled setting leads to a strategic action of hiding negative emotions and avoiding any expression of dissatisfaction. This subsequently leads to a prudence in the prospective adopters' actions as they are acutely aware of the delicacy of the situation and the importance of 'playing their cards right' (Noordegraaf, Nijnatten and Elbers, 2010). This can result in strategies that maximise personal gain but hinder reflection and honesty.…”
Section: Discussionmentioning
confidence: 99%
“…In five studies, researchers followed a phenomenon from text to talk, or talk to text. For instance, the studies showed how social workers included and omitted aspects of clients’ talk in documents (Arminen and Perälä, 2002; Noordegraaf et al, 2009a), and how clients’ interactional conduct was used in texts as proof of their character or relationships (Noordegraaf et al, 2010).…”
Section: Methodsmentioning
confidence: 99%